A NATIONAL APPROACH TO CLINICAL GENOMICS. (February 2015) - Sinclair, Andrew
Abstract : Several countries have recognised the need for a national effort to address the challenges and potential value of genomics, but each have adopted different approaches. Genome Canada provides substantial funding to six major centres across the country to drive genomics across a range of endeavours to benefit the whole economy. Recently, the UK government has set up Genomics England, to deliver the 100, 000 genomes project that aims to create a lasting legacy for patients, the NHS and the UK economy. The Australian context shares some similarities with these countries: clinical genetics is delivered predominantly in a public health care system and services are dispersed geographically. However, by contrast Australian genetic services are largely embedded in state-funded health systems. An Australian national approach needs to be federated respecting state responsibilities, while addressing areas of national value. I will discuss progress by a coalition of clinical genetic services, diagnostic laboratories and research institutes from all states that are developing a coordinated national approach to the implementation of genomics into the Australian healthcare system.